Federalism and confederate stances in the political speech of independent Brazil: the concepts in the writings of Frei Caneca - Leme, Maria Saenz (Universidade Federal de São Paulo - UNIFESP, 2017)
Abstract: This study analyses the understanding of federation and confederation that can be seized from the writings of Frei Caneca, produced during the independence process of Brazil and the beginning of the First Reign. These terms were used interchangeably in the period and spanned with the same intensity different political notions that were juxtaposed at the time, involving the sovereignty of a developing national state and the emphases on how provincial autonomy was considered. The Federalist Papers, a classical work for the notional understanding of the liberal state's formation in its federative dimension, will be used as a theoretical counterpoint to this debate.

Resumo: No presente artigo problematizam-se os entendimentos de federação e confederação que se podem apreender nos escritos de Frei Caneca, elaborados durante o processo de Independência do Brasil e início do Primeiro Reinado. Nesse período esses termos se empregavam de modo indistinto e abrangiam num mesmo diapasão diferenciadas concepções políticas que então se contrapunham, envolvendo a soberania do estado nacional em formação e as ênfases no modo de se pensar a autonomia provincial. Como contraponto teórico para esse debate, utilizam-se Os Artigos Federalistas, obra clássica para a compreensão conceitual da formação do estado liberal em sua dimensão federativa.
Federalismo e posturas confederativas no discurso político do Brasil independente: as concepções dos escritos de Frei Caneca
Keywords: Liberalism - provinces - federation - confederation; Liberalismo - províncias - federação - confederação